Study on Transportation Mode Choice Among Full-Time Students in Jakarta - Sumarmi, Sumarmi; Kinasih, Reni Karno; Firdaus, Hendy Yusman; Nabila, Nabila (Universitas Mercu Buana, 2024)
University students, as a significant demographic group in urban environments, play a crucial role in daily commuting activities. Understanding their travel patterns and transportation mode preferences is essential for promoting sustainable and efficient urban planning. This study aimed to evaluate students' transportation mode preferences using the Analytical Hierarchy Process (AHP), a Multi-Criteria Decision-Making (MCDM) method, processed through Expert Choice software.Data were collected via questionnaires distributed to 119 full-time students. The analysis considered four main criteria: cost (C1), flexibility (C2), reliability (C3), and comfort (C4), across three transportation modes: private vehicles (M1), public transport (M2), and online-based transportation (M3). Results indicate that the majority of students (64.2%) prefer private vehicles, with cost being the most influential criterion (60.9%), followed by flexibility (20.8%), reliability (10.7%), and comfort, which was the least influential criterion (7.6%). This study provides valuable insights for policymakers to design urban transportation systems that better address the needs of university students.